DEVELOPMENT OF NAHWU EDUCATIONAL T-SHIRTS TO IMPROVE STUDENTS' ARABIC GRAMMAR LEARNING - Ihwan Rahman Bahtiar; Mohamad Sarip; Chakam Faliasuf; Khotimatun Nafi'ah; Nuruddin; Andri Ilham (Jurnal Ilmiah Bina Bahasa, 2026)
The study aims to develop and evaluate the feasibility of Nahwu Educational T-shirts, a wearable instructional media designed to support visual and contextual learning of Arabic grammar (Nahwu). The study employed a research and development methodology based on the four-D model, comprising the stages of definition, design, development, and dissemination. The subjects were students in the Arabic language program at Universitas Negeri Jakarta. Data collection used expert validation sheets, questionnaires, and interviews. The analysis used descriptive, quantitative, and qualitative methods. The results show that the product is highly practical, with mean validation scores of 3.46 from material experts and 3.50 from design experts. During the dissemination survey, 87.5% of students considered the product innovative, 79% said the media engaged them more with the material, and 75% reported it helped them learn Nahwu concepts. It demonstrates that integrating grammatical content into contextual and visual media can increase students’ interest and understanding of Arabic syntax. Nahwu educational T-shirts are a modest yet practical and effective visual learning tool that makes Arabic grammar instruction more engaging and contextually meaningful.